Risk factors associated with the presence of irreversible airflow limitation and reduced transfer coefficient in patients with asthma after 26 years of follow up. Issue 4 (1st April 2003) - Vonk, J M; Jongepier, H; Panhuysen, C I M; Schouten, J P; Bleecker, E R; Postma, D S
Abstract : Background: Childhood asthma is generally believed to be a disorder with a good prognosis. However, some asthmatics develop irreversible airway obstruction, probably as a result of airway remodelling. Methods: After 21–33 years, 228 adults (aged 13–44 years at baseline) with a history of asthma were re-examined to assess risk factors for the development of irreversible airway obstruction (IAO, forced expiratory volume in 1 second (FEV1 ) <80% predicted and reversibility <9% predicted) and a reduced postbronchodilator transfer coefficient (carbon monoxide transfer factor/alveolar volume, <80% predicted), both characteristics of COPD. Results: At follow up, 41% did not have airway obstruction (NAO), 43% had reversible airway obstruction (RAO), and 16% had IAO; 23% had a reduced transfer coefficient. Patients with RAO had asthma-like characteristics (wheezing, asthma attacks, bronchial hyperresponsiveness (BHR)) while patients with IAO had COPD-like symptoms (cough, phlegm, dyspnoea) at follow up. The development of IAO is determined by a lower FEV1, less reversibility of airway obstruction and, surprisingly, less severe BHR at initial screening. Eighty percent of the patients with asthma who used anti-inflammatory medication still had airway obstruction, but IAO developed less frequently. Smoking was associated with a reduced transfer coefficient but not with the development of IAO. Female sex was associated with a reduced transfer coefficient, whereas corticosteroid use was not. Conclusions: Although IAO and a low transfer coefficient are both characteristics of COPD, they represent distinct entities in adult asthmatics in terms of symptomatology, aetiology, and probably in therapeutic approaches and disease prevention.